La Suspensión Condicional del Procedimiento, como Mecanismos Alternativo de Solución de Conflictos al Proceso Penal, debe ser Incorporada en el Código Orgánico Integral Penal, en los Procedimientos Especiales, para Garantizar el Principio de Mínima Intervención Penall - Carrión Jiménez, Eddy Leonel (2018)
The present thesis entitled “ The Conditional Suspension of the Procedure, as alternative mechanism of conflicts solutions to the criminal process, must be incorporated in the Integral Organic Criminal Code, in the special procedures, to ensure the principle of Minimum Criminal Intervention ", the non-application of the conditional suspension of the procedure in the Criminal integral Organic Code, implies the non-application of the principle of minimum criminal intervention and opportunity, principles that having constitutional ranges, must be applied to all processed people in a criminal judgment, however, these principles are not being looked when the accused is submitted to all stages of the process, instruction, evaluation and judgment preparatory and the judgment, so that at the end a conviction is issued and at that time they can be take advantage for an alternative solution to the process; the principle of minimum criminal intervention builds a benefit in favor of the processed, according to which the processed accepted the facts that are imputed to them, repairing the damages caused to the victim, taking into account that the crime for which the processed is accused does not exceed five years of imprisonment and fully complying with the conditions imposed by the judge and they not be immersed in the prohibitions of the same. The article 195 of the Ecuador Republic Constitution indicates the principle of minimum intervention and opportunity, has special attention to the public interests and the victim’s rights. That is how it ensures the application of the last ratio principle, in the 5 criminal procedures which are not a biggest social commotion or shock and they do not be submit to a long criminal process as actually. The theoretical, legal and doctrinal information, the surveys and interviews applications, allowed to get criteria with clear and precise bases of a recognized bibliography, which contributed to the objectives verification and to the contrast of the hypothesis raised regarding to this practice; Both the Ecuador Republic Constitution and the Comprehensive Organic Criminal Code ensure the minimal criminal intervention as the principle of opportunity, which is applied in a timely, nimble and effective way to all infringement committed in all criminal process, provided that they comply with the requirement for its application; taking as reference the special criminal procedure of the conditional suspension of the procedure which involve the acceptance of the accused, to submitt to this procedure; fulfilling the established budgets; as well as the conditions and deadlines set by the judge at the hearing; the purpose that verified the suspension fulfillment, the cause file is dictated and therefore the criminal action is declared extinct.